(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The objective was to determine the degree of correlation between the effect of Covid 19 and teaching performance in the educational institutions of UGEL 03 Cercado, Lima - Peru, 2022. It is important to indicate that this study confirms the generalized prevalence of the effect of Covid 19 and teaching performance, which is related to how other studies have shown that it affects the academic performance of students. The method used was the hypothetical deductive, descriptive, and cross-sectional correctional design. The population consisted of 60 regular elementary school teachers. Data were obtained by means of a survey and two questionnaires based on the Likert scale were used as instruments. The same data were processed through the Spearman rho statistical analysis. The results indicate that there is a 0.859 correlation between both variables.